A homozygous R148W mutation in Semaphorin 7A causes progressive familial intrahepatic cholestasis. Issue 11 (29th September 2021) - Pan, Qiong; Luo, Gang; Qu, Jiaquan; Chen, Sheng; Zhang, Xiaoxun; Zhao, Nan; Ding, Jingjing; Yang, Hong; Li, Mingqiao; Li, Ling; Cheng, Ying; Li, Xuan; et al.
Abstract: Semaphorin 7A (SEMA7A) is a membrane‐bound protein that involves axon growth and other biological processes. SEMA7A mutations are associated with vertebral fracture and Kallmann syndrome. Here, we report a case with a mutation in SEMA7A that displays familial cholestasis. WGS reveals a SEMA7A R148W homozygous mutation in a female child with elevated levels of serum ALT, AST, and total bile acid (TBA) of unknown etiology. This patient also carried a SLC10A1 S267F allele, but Slc10a1 S267F homozygous mice exhibited normal liver function. Similar to the child, Sema7a R145W homozygous mice displayed elevated levels of serum ALT, AST, and TBA. Remarkably, liver histology and LC‐MS/MS analyses exhibited hepatocyte hydropic degeneration and increased liver bile acid (BA) levels in Sema7a R145W homozygous mice. Further mechanistic studies demonstrated that Sema7a R145W mutation reduced the expression of canalicular membrane BA transporters, bile salt export pump (Bsep), and multidrug resistance‐associated protein‐2 (Mrp2), causing intrahepatic cholestasis in mice. Administration with ursodeoxycholic acid and a dietary supplement glutathione improved liver function in the child. Therefore, Sema7a R145W homozygous mutation causes intrahepatic cholestasis by reducing hepatic Bsep and Mrp2 expression. SYNOPSIS: A new type of progressive familial intrahepatic cholestasis (PFIC) was caused by the homozygous R148W mutation in SEMA7A. Preliminary mechanistic studies revealed that the mutation reduced hepatic expression of canalicular membrane bile acid (BA) efflux transporters Bsep and Mrp2, resulting in intrahepatic cholestasis. A female child patient presented with elevated levels of serum ALT, AST, and total bile acid (TBA) of unknown etiology. A SEMA7AR148W homozygous mutation was identified in the child patient. The Sema7aR145W (human R148W) homozygous mice displayed elevated levels of serum ALT, AST, and TBA, as well as hepatocyte hydropic degeneration and intrahepatic accumulation of conjugated BAs. The Sema7aR145W homozygous mutation reduced the expression of canalicular membrane Bsep and Mrp2 in mouse livers and sandwich‐cultured primary hepatocytes. Administration with ursodeoxycholic acid (UDCA) and a dietary supplement glutathione (GSH) were effective for this new type of PFIC. Abstract : A new type of progressive familial intrahepatic cholestasis (PFIC) was caused by the homozygous R148W mutation in SEMA7A. Preliminary mechanistic studies revealed that the mutation reduced hepatic expression of canalicular membrane bile acid (BA) efflux transporters Bsep and Mrp2, resulting in intrahepatic cholestasis.